Fabrication and characterizations of keratin hydrogel for tissue engineering - Chong, Ka Xin (2015)
Keratin is a natural protein that is abundant and easily found in animal structures such as hair, hooves, horns and nails. This material is attractive as it possesses high biocompatibility, biodegradability, neuroinductivity and flexibility to be made into different forms. Besides that, keratin can give considerable mechanical properties as strong intermolecular and intramolecular chemical crosslinks can be achieved within the structure, most significantly is through disulphide bonds. In this report, the raw material to form keratin hydrogel, keratin itself was first extracted from discarded human hair. Utilizing the extracted keratin solution, hydrogels of different concentrations were produced. The higher concentration of hydrogel was achieved by the elimination of low molecular weight Keratin Associated Proteins (KAPs). After all the fabrications, various quantification and characterization techniques were used to study the hydrogels. The methods include PierceTM 660nm Protein Assay, Attenuated Total Reflectance Fourier Transform Infrared (ATR-FTIR), Thermal Gravimetric Analysis (TGA), Scanning Electron Microscopy (SEM), Rheology and Differential Scanning Calorimetry (DSC). Discussions were carried out for all the results obtained from the above different techniques. An unexpected data was collected whereby the less concentrated hydrogel was found to have a denser structure than the more concentrated hydrogel. Lastly, some possible further improvements were dictated in the recommendations section.